MEMETAKAN WACANA KONTEMPORER PENDIDIKAN AGAMA ISLAM: ANALISIS BIBLIOMETRIK TEMA EKOLOGI,MODERASI, DAN TEKNOLOGI (2010-2025) - Ardian Al Hidaya; Nurul Anisa; Efriliana Putri Nasution; Arif Fikri; Misronida Harahap (Yayasan Baitul Hikmah al-Zain, 2026)
This study aims to map the thematic evolution of Islamic Religious Education (PAI) research from 2010 to 2025, focusing on three contemporary discourses: religious moderation, Islamic ecology (eco-Islam), and science-technology integration. Bibliometric and sciencemapping methods were applied to 1,000 publications from Crossref, analyzed using VOS viewer based on title and abstract text mining. The co-occurrence analysis revealed an unequal intellectual structure: the religious moderation and character education clusters dominate as highly cohesive mainstreams, reflecting a strong response to Indonesia's socio-political context. Meanwhile, the digital transformation discourse forms a separate cluster with high citation influence but limited thematic integration. Critically, the discourse on Islamic environmental ethics (eco-Islam) emerges as an isolated cluster, marking a glaring research gap despite its solid theological foundation. An overlay analysis reveals moderation as an established theme, while environmental issues and artificial intelligence are emerging topics that have not yet been integrated. The study's conclusion highlights the need for an integrative research agenda to weave together these three discourses to address 21st-century challenges more holistically.